2003
DOI: 10.1046/j.1360-0443.2003.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Prior opiate injection and incarceration history predict injection drug use among inmates

Abstract: The possibility of transmission of human immunodeficiency virus (HIV), hepatitis C (HCV) or other blood-borne diseases exists in Ontario correctional centres. In this setting, drug injection while incarcerated is primarily related to opiate use prior to incarceration. The correlation between injecting and extensive incarceration history suggests missed opportunities to improve inmates' health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 31 publications
8
40
1
1
Order By: Relevance
“…However, previous research in this area has documented drug use in prison environments using this approach (Boys et al, 2002; Calzavara et al, 2003; Gillespie, 2005; Inciardi, Lockwood, & Quinlan, 1993; Kinner, Jenkinson, Gouillou, & Milloy, 2012; Small et al, 2005), and self-reported drug use among this sample was also shown to be more valid than medical record data in a separate analysis (Bai et al, 2014). …”
Section: Resultsmentioning
confidence: 81%
“…However, previous research in this area has documented drug use in prison environments using this approach (Boys et al, 2002; Calzavara et al, 2003; Gillespie, 2005; Inciardi, Lockwood, & Quinlan, 1993; Kinner, Jenkinson, Gouillou, & Milloy, 2012; Small et al, 2005), and self-reported drug use among this sample was also shown to be more valid than medical record data in a separate analysis (Bai et al, 2014). …”
Section: Resultsmentioning
confidence: 81%
“…History of incarceration was significantly associated with opiate use for both men and women, however, from the current study we do not know if drug use occurred only in jail/prison, only during those periods when the participants were not incarcerated, or both. While incarceration was significantly associated with injection drug use, the Anderson model posits multiple vulnerabilities (Calzavara et al 2003) as pathways to health services usage. The total mediated effect (indirect effect) of opiate use in this study was significant only for men suggesting that opiate use is a vulnerability for men but not for women in terms of ED use.…”
Section: Discussionmentioning
confidence: 99%
“…Incarceration and drug use prior to incarceration have been associated with injection drug use among inmates (Calzavara et al 2003). Prisons may be high-risk environments for the initiation and use of heroin and other drugs (Boys et al 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although it is clear that high-risk behaviors occur in incarcerated settings 38,[45][46][47] and that reduction in risk behavior can occur with the use of methadone, 39 variability of prison systems and settings in different regions may imply that optimal methadone treatment policies should be tailored to local conditions. Providing MMT for inmates who were treated in community clinics prior to incarceration or initiating MMT in the incarcerated setting may also be an effective strategy to prevent HIV and hepatitis transmission in settings where high-risk behaviors are prevalent [46][47][48] and where effective linkage to community-based treatment exists for the post-release period. Two considerations in deciding the political feasibility and advisability of initiating prison-based MMT are whether high-risk behaviors or intraprison disease transmission is evident 48,49 and whether effective linkage to community MMT is present.…”
Section: Discussionmentioning
confidence: 99%